SSL/TLS: analysis of Bleichenbacher's attack - Li, Jin Xuan (Nanyang Technological University, 2024)
This report provides an analysis of the Bleichenbacher’s attack on the Secure Sockets Layer (SSL) and Transport Layer Security (TLS) protocols, which are crucial for secure internet communication. The report begins with an introduction to the importance of SSL/TLS in secure communication and sets the scope and objectives of the study. The second chapter lays the foundation by discussing the RSA Cryptosystem, the Public Key Cryptosystem Standards, and the SSL/TLS protocol while highlighting their relations. The third chapter is dedicated to the Bleichenbacher’s attack itself. It starts with an overview of the attack and its historical context. The chapter then delves into the intuition behind the attack and presents a detailed walkthrough of the algorithm, explaining each step and its purpose. The chapter also introduces the different oracle types used in the attack and demonstrates the attack through a proof-of-concept, discussing the experimental results. The fourth chapter focuses on the countermeasures introduced over the years to mitigate the Bleichenbacher’s attack. The fifth chapter explores the optimization methods discovered to speed up certain steps in the original algorithm, discussing their rationale, implementation, and impact on the attack’s efficiency. The report concludes with a summary of the key takeaways, the implications of the study, and suggestions for future research directions.The bibliography section provides the references used throughout the report. This study contributes to the understanding of the Bleichenbacher’s attack on SSL/TLS and the ongoing efforts to secure these essential protocols against such threats.